2021
DOI: 10.1177/01461672211060965
|View full text |Cite
|
Sign up to set email alerts
|

Can Conspiracy Beliefs Be Beneficial? Longitudinal Linkages Between Conspiracy Beliefs, Anxiety, Uncertainty Aversion, and Existential Threat

Abstract: Research suggests that conspiracy beliefs are adopted because they promise to reduce anxiety, uncertainty, and threat. However, little research has investigated whether conspiracy beliefs actually fulfill these promises. We conducted two longitudinal studies ( NStudy 1 = 405, NStudy 2 = 1,012) to examine how conspiracy beliefs result from, and in turn influence, anxiety, uncertainty aversion, and existential threat. Random intercept cross-lagged panel analyses indicate that people who were, on average, more an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 64 publications
2
67
1
4
Order By: Relevance
“…While there is a strong evidence base for the psychological underpinning of conspiracy beliefs, less is known about the consequences [ 9 ]. This article has illuminated a range of consequences of conspiracy theorising, from impacting global issues such as vaccine uptake to worsening intergroup relations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While there is a strong evidence base for the psychological underpinning of conspiracy beliefs, less is known about the consequences [ 9 ]. This article has illuminated a range of consequences of conspiracy theorising, from impacting global issues such as vaccine uptake to worsening intergroup relations.…”
Section: Discussionmentioning
confidence: 99%
“…If conspiracy beliefs are alluring as a means to address psychological needs, then a positive consequence of endorsing these beliefs could be assumed to remedy negative feelings. To test this, Liekefett and colleagues [ 9 ] conducted two longitudinal studies over a 6-week and 1-year time frame, tracking individuals’ conspiracy beliefs, anxiety, uncertainty aversion and threat perception. Findings revealed that conspiracy beliefs did not reduce anxiety, uncertainty aversion, or existential threat, and there was some evidence that it increased these negative feelings and reinforced conspiracy beliefs.…”
Section: Introductionmentioning
confidence: 99%
“…However, less is known about the relative and absolute nature of these relationships, such as whether some motives play a more central role than others (see van Prooijen, 2020), or whether these beliefs actually satisfy the needs that motivate their endorsement in the first place (cf. Liekefett et al, 2021). Other ambiguities exist with regards to whether beliefs in conspiracy theories serve to challenge or defend the status quo (e.g., Jolley et al, 2018), are harmful or constructive to personal well-being (Cichocka, 2020;Douglas et al, 2015), and whether they should be seen as a threat to, or even a manifestation of the natural processes of a democratic society (Douglas et al, 2019).…”
Section: Belief In Conspiracy Theoriesmentioning
confidence: 99%
“…However, there is no specific accepted time interval between different phases of data collection ( Cole and Maxwell, 2003 ). However, in recent scholarly work, researchers have maintained a temporal separation of 2 weeks to control the common method bias without losing the effect of the predictor on the outcome ( Raja et al, 2018 ; Liekefett et al, 2022 ). Consistent with the existing practice, we followed a temporal separation of 2 weeks in our data collection.…”
Section: Methodsmentioning
confidence: 99%